Las ONG´S y los sistemas administrativos y contables; Diseño de un manual de procedimientos de control interno para la corporación ABYA - YALA. - Quevedo Ruiz, Edwin Alejandro (2011)
This research was developed in ABYA – YALA Corporation. It is aimed at defining the need for Internal Control System Non – Governmental Organizations, it arises from the weakness in the administration of the economic and financial resources, considering the system as an administrative support to the Accounting Management by developing of a manual of administrative procedures that will serve as a guide to the operations of the people who collaborate with the Organization. In this investigation used the type of field because it was presented by manipulating of en external variable unproven, in order describe what or why reasons produce a particular situation on event. In addition the people involved. For this work was handle non – experimental methodology, using statistical methods such as: percentages tables, pie charts, and analysis and interpretation of results. Also the technique use was the Survey, it was applied to the Board of Directors, Manager, Accountant, Accountant Assistant, Technical Coordinator, Field Technical and General Service staff to know if the actors use the Internal Control System as a fundamental base for the defense of their economic and financial resources. With the present study aims to benefit to the ABYA – YALA Corporation from Latacunga city; because this document will become a tool to improve the control of the resources and increase the chance of obtaining financing in the community because it ensures that funds of investment are channeled to the projects properly; to the university because it allows the Social projects; and; to the students because it is a reference tool for future investigations of the same or similar characteristics.